PEMBERIAN PENYULUHAN PROGRAM KESEHATAN SERTA PENCEGAHAM PENYEBARAN VIRUS DI MASA PANDEMI COVID 19 DI PANTI ASUHAN “YATIM” MOJOKERTO - Erry Setiawan; Dwi Dewianawati; Ratna Agustina (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of this study was to find out the form of counseling on the COVID-19 pandemic to the Orphan Orphanage (PAY), a description of the attention paid to preventing the spread of the Orphan Orphanage (PAY) virus and to describe the supporting factors for the Orphan Orphanage (PAY) in the spread of the covid 19 virus. The research method used in this study is a direct home service method, where the Orphan Orphanage (PAY) will be visited by Advisors and Students in the hope of providing counseling and ways to deal with the spread of the covid virus and delivering basic food assistance to improve prosperity and is expected to provide self-motivation for the children of the Mojokerto City Orphan Orphanage (PAY). Based on the home care research method, it was carried out in socializing the dangers of covid through 3M health program counseling and the use of these tools by practicing in front of the students and administrators, while handling the spread of the virus involved all students and administrators assisted by students in cleaning the area and place at the orphanage. The orphans and the use of 3M traps in the area. Meanwhile, during this pandemic, the Orphan Orphanage is also a distributor of formula drugs that increase immunity to maintain health and fortify themselves from the covid 19 virus who are members of the Muhammadiyah Covid 19 Command Center community in East Java and there is also bee honey cultivation as the management of the orphanage's own children as honey distributors. In this KKN activity, they provided counseling about Covid-19, and welfare motivation in the form of providing basic food items in addition to donations to the Mojokerto City Orphan Orphanage (PAY). Through the activity of providing basic food items and health supporting